Mengasah Kepercayaan Diri Siswa Melalui Pelatihan Public Speaking di MAN 2 Lampung Utara - Winalda, Tio; Nurmala, Intan; Anjelina, Diah Ayu; Sari, Diani; Muinah; Gunanto, Sigit; Ningrum, Fhela Vhantoria (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2025)
Public speaking is an essential part of communication skills that are not easily mastered by everyone. Anxiety about speaking in public often hinders individuals from developing. The negative impacts can be seen from the physical and emotional health disorders they experience. Lack of confidence when speaking in public is also experienced by students of MAN 2 North Lampung. The right solution is to hold public speaking training that can build students' confidence in speaking in public. The approach is a sequence of training sessions that are precisely and clearly organized within a given time period, tailored to the organizer's time and location available. The activity's outcomes demonstrate that a large number of high school students are interested in public speaking, and we can observe that each student has good potential when it comes to public speaking practice. The inference that may be made is that public speaking abilities are fundamental and should be had by everyone, particularly high school pupils who will find them valuable in the future.